2013
DOI: 10.1186/1471-244x-13-89
|View full text |Cite
|
Sign up to set email alerts
|

Positive resources for combating depressive symptoms among Chinese male correctional officers: perceived organizational support and psychological capital

Abstract: BackgroundAlthough correctional officers (COs) clearly suffer from depression, positive resources for combating depression have been rarely studied in this population. The purpose of the study was to examine the associations of perceived organizational support (POS) and psychological capital (PsyCap) with depressive symptoms among Chinese COs.MethodsA cross-sectional survey was conducted in a province of northeast China during March–April 2011. A self-administered questionnaire was distributed to 1900 male COs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
99
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 36 publications
8
99
0
8
Order By: Relevance
“…The present study indicated that POS may be a highly effective resource that can help underground miners combat depression and anxiety. This result was consistent with previous studies in which other occupational groups from different countries with supportive organizations were more likely to show mental well-being 15,20) . The internal coping resources of mental health problems include ability, personality trait, coping style, and so on.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The present study indicated that POS may be a highly effective resource that can help underground miners combat depression and anxiety. This result was consistent with previous studies in which other occupational groups from different countries with supportive organizations were more likely to show mental well-being 15,20) . The internal coping resources of mental health problems include ability, personality trait, coping style, and so on.…”
Section: Discussionsupporting
confidence: 83%
“…The mean level of depressive symptoms was higher than that of other male occupational groups in China, such as correctional officers 20) and a cross-occupational sample including teachers, foreign enterprise employees, managers, researchers, traffic police and community health workers from Shanghai 23) . This was consistent with the level of Chinese male doctors 24) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations